Roh Kudus dan kehidupan sosial politik: Sebuah tawaran peranan Roh Kudus dalam tanggung jawab sosial politik Gereja - Sitanggang, Asigor Parongna (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
Too often the work of the Holy Spirit is reduced to mere personal, interpersonal, or ecclesial dimensions which becomes subjective, and unrelated to the social-political life in the public space. This is a common perspective that we see in the churches. On the contrary, the Scripture places a great emphasis on the social and global dimension of the Holy Spirit who, in the Nicene Creed, is called the Giver of Life. This paper will discuss the socio-political dimension of the Holy Spirit. The method used in this paper is literary research. This paper is based on the idea that the Holy Spirit works not only in a personal, interpersonal, or ecclesial dimension, but has a strong socio-political dimension, which in that way we can truly understand and involve ourselves in the work of the Spirit in the socio-political life of each of us. AbstrakKarya Roh Kudus terlalu sering direduksi hanya pada dimensi personal, interpersonal, ataueklesial belaka. Padahal, Kitab Suci sangat menekankan dimensi sosial dan global dari Roh Kudus yang, dalam Kredo Nicea, disebut sebagai Pemberi Kehidupan (the Giver of Life). Makalah ini akan membahas dimensi sosial-politik dari Roh Kudus sehingga kita dapat sungguh memahami dan melibatkan diri dalam karya Roh di dalam kehidupan sosial-politik kita masing-masing.